Oxidan - Jaʻfarī, Amīr; Aghapour, Vahid; Behbudi, Reza (Filmhub, 2024)
Aslan's fiancée Negar is leaving the country illegally and without informing him. Now, he is after a way to get a visa to try and get her back.